PELAKSANAAN PROGRAM KELUARGA BERENCANA (KB) DI KECAMATAN BARAKA KABUPATEN ENREKANG - Jusliati Jusliati; Kadir Adys; Nasrulhaq Nasrulhaq (Department of Public Administration, Muhammadiyah University of Makassar, 2018)
This study aimed to find out. Implementation of Family Planning Program in Baraka District, Enrekang Regency. The type of research used in this study was descriptive qualitative research with phenomenology that was inductive. Data collection techniques used by researchers were interviews with eight informants, observation, and documentation. Data analysis techniques used were data reduction, data presentation, data presentation, and conclusion. Data validity was used triangulation that was source triangulation, triangulation time, and triangulation technique. The results of this study indicated that the Family Planning Program seuccessfully run well wuth evidence that the satisfaction of people who had used KB, but still needed to improve access to quality services in Family Planning Program in Baraka District Enrekang Regency Keywords implementation of Family Planning Program (KB).Key words: The implementation of Family Planning Program (KB).